Sustaining Student Engagement in Chinese Higher Education: A Qualitative Study of Social Support and Motivation - Zhang, Shu; Anuar Bin Ahmad; Jamsari Bin Alias (Journal of Qualitative Research in Education, 2026)
Sustainable learning participation has emerged as a key issue in higher education, especially in situations where academic pressure and the speed of change in education are high. This paper looks at the role of social support and motivation in maintaining student engagement in the long run amongst Chinese university students. This research is designed to examine the effect of social support processes and motivation processes on maintaining long-term learning engagement in postsecondary education. The semi-structured interviews took place with 25 undergraduate and postgraduate students from Chinese public universities. NVivo-assisted thematic analysis was used in analyzing data through an interpretivist paradigm. The concept of sustainable engagement that will be used in this research is the ability of students to be able to recover and re-engage when they are disengaged, as opposed to being continuously motivated. The experience of sustainable learning is dynamic and thus cycles of disengagement and recovery, and not constant motivation. Relational support provided by family, peers, teachers, and institutions plays the role of psychological and structural infrastructure, which helps in sustaining persistence and re-engagement. Intrinsic interest, future orientation, self-efficacy, and perceived meaning are motivation factors that are very important resources that promote engagement in the long run. This research will add to the body of literature on engagement by offering a conceptualization of sustainable engagement as a process of recovery and illustrating a reciprocal interaction between social support and motivation in the formation of long-term engagement. The results serve as qualitative information to teachers and schools that would want to create enabling learning conditions that support persistence and student wellness.